The insect‐focused classification of fruit syndromes in tropical rain forests: An inter‐continental comparison. (28th January 2019) - Dahl, Chris; Ctvrtecka, Richard; Gripenberg, Sofia; Lewis, Owen T.; Segar, Simon T.; Klimes, Petr; Sam, Katerina; Rinan, Dominic; Filip, Jonah; Lilip, Roll; Kongnoo, Pitoon; Panmeng, Montarika; et al.
Abstract: We propose a new classification of rain forest plants into eight fruit syndromes, based on fruit morphology and other traits relevant to fruit‐feeding insects. This classification is compared with other systems based on plant morphology or traits relevant to vertebrate fruit dispersers. Our syndromes are based on fruits sampled from 1, 192 plant species at three Forest Global Earth Observatory plots: Barro Colorado Island (Panama), Khao Chong (Thailand), and Wanang (Papua New Guinea). The three plots differed widely in fruit syndrome composition. Plant species with fleshy, indehiscent fruits containing multiple seeds were important at all three sites. However, in Panama, a high proportion of species had dry fruits, while in New Guinea and Thailand, species with fleshy drupes and thin mesocarps were dominant. Species with dry, winged seeds that do not develop as capsules were important in Thailand, reflecting the local importance of Dipterocarpaceae. These differences can also determine differences among frugivorous insect communities. Fruit syndromes and colors were phylogenetically flexible traits at the scale studied, as only three of the eight seed syndromes, and one of the 10 colors, showed significant phylogenetic clustering at either genus or family levels. Plant phylogeny was, however, the most important factor explaining differences in overall fruit syndrome composition among individual plant families or genera across the three study sites. Abstract in Melanesian is available with online material.